Leishmania metacyclogenesis is promoted in the absence of purines. - Tiago Donatelli Serafim (Public Library of Science (PLoS), 2012)
Leishmania parasites, the causative agent of leishmaniasis, are transmitted through the bite of an infected sand fly. Leishmania parasites present two basic forms known as promastigote and amastigote which, respectively, parasitizes the vector and the mammalian hosts. Infection of the vertebrate host is dependent on the development, in the vector, of metacyclic promastigotes, however, little is known about the factors that trigger metacyclogenesis in Leishmania parasites. It has been generally stated that "stressful conditions" will lead to development of metacyclic forms, and with the exception of a few studies no detailed analysis of the molecular nature of the stress factor has been performed. Here we show that presence/absence of nucleosides, especially adenosine, controls metacyclogenesis both in vitro and in vivo. We found that addition of an adenosine-receptor antagonist to in vitro cultures of Leishmania amazonensis significantly increases metacyclogenesis, an effect that can be reversed by the presence of specific purine nucleosides or nucleobases. Furthermore, our results show that proliferation and metacyclogenesis are independently regulated and that addition of adenosine to culture medium is sufficient to recover proliferative characteristics for purified metacyclic promastigotes. More importantly, we show that metacyclogenesis was inhibited in sand flies infected with Leishmania infantum chagasi that were fed a mixture of sucrose and adenosine. Our results fill a gap in the life cycle of Leishmania parasites by demonstrating how metacyclogenesis, a key point in the propagation of the parasite to the mammalian host, can be controlled by the presence of specific purines.